Key health impacts and support systems for informal carers in the UK: A thematic review - Susanna A Cottagiri; Peter Sykes (Journal of Health and Social Sciences)
Introduction: The economic contributions made by informal carers in the UK per year mount up to £132 billion. This is equivalent to the total amount of the health care costs, yet the health and wellbeing of carers are often not prioritised. This review paper aims to determine the key health impacts of informal caregiving and evaluate support/control methods in the UK. Methods: This thematic review was conducted in accordance with an adapted version of the PRISMA guidelines for systematic reviews. Of the 6,482 articles identified through Pubmed/Medline, CINAHL, SpringerLink, Summon, and grey literature, 38 studies were included in the review. Results: The key health impacts of being an informal carer were identified as musculoskeletal disorders and psychological issues (such as depression, stress and anxiety), which were categorized as ‘high-risk impact’ areas. The review further identified cardiovascular disease and early mortality as ‘low to moderate risk impact’ areas and a thematic area that revolves around positive impacts on health of informal carers. Financial help, proper respite care, availability and accessibility of information and advice, provision of equipment in a timely manner and adequate support networks were found to be key factors useful in minimising musculoskeletal and psychological disorders. Discussion and Conclusions: There is a need for policy makers and program implementers to recognize and accommodate the ever-changing role of carers on different stages of caring. There is also a need to review key health policy documents to include informal carers’ needs and improve support systems available. The lack of evidence-based research on the psycho-physical impacts of caring and the lack of evaluation of services that impact the health of carers also needs to be addressed with priority.